Variations in the concentration of magnesium stearate as a lubricant in the evaluation test results of paracetamol tablet preparations - Agnes Widian; Dimas Bagus Cahyo (Strada Journal of Pharmacy, 2019)
Tablets are an oral drug preparation that can be formulated with or without additional substances. This preparation has many advantages, one of which is that it is practical to use and can be produced on a large scale. Tablets are produced using 3 methods, namely dry granulation, wet granulation and direct compression. Each manufacturing method must be adapted to the tablet material to be printed. So it is necessary for formulators to know the characteristics of the materials to be used.Tablet production involves excipients or additional substances which have an important role. Excipients are one of the considerations in preformulation studies to determine the right characteristics and quantities to produce tablets that meet the requirements. One of the excipients in tablet formulation is a binder. So far tablet binders are divided into 2 types, namely natural polymer binders and synthetic polymer binders. Additional materials play 2 important roles in making tablets, one of which is the binder. The binder is intended to provide tablet compactness and durability so that the binder guarantees the integration of several powder particles into a granulate (Oktavia, 2011). Granulation is a process of increasing the size of small powder particles that are bound together to become large ones that can flow freely. The purpose of granulation is to make the mass flow freely, compact the mixture of ingredients, create a uniform mixture that does not separate, improve the compressibility characteristics of the active substance, control the speed of release of the active substance from the dosage form, reduce dust and improve the appearance of the tablet (Lachman, 1994). Observation of the results of evaluating the physical quality of the preparation includes organoleptic tests, hardness test, brittleness test, disintegration time test and weight uniformity test. The results of this research based on the friability test, the F1 result was 0.74%, fulfilling the requirements of the tablet friability test, namely, no more than 0.8% loss of the total mass of the FI 3rd edition tablet. 4. The results of the tablet uniformity test show that there is not a single tablet whose weight deviates from column A, namely more than 5% and there is not a single tablet whose weight deviates from column B, namely more than 10% from the average weight in F1. All tablets in FI have a uniform tablet weight with no deviation so that FI complies with the specified range requirements.